Genistein: An Integrative Overview of Its Mode of Action, Pharmacological Properties, and Health Benefits. (20th July 2021) - Sharifi-Rad, Javad; Quispe, Cristina; Imran, Muhammad; Rauf, Abdur; Nadeem, Muhammad; Gondal, Tanweer Aslam; Ahmad, Bashir; Atif, Muhammad; Mubarak, Mohammad S.; Sytar, Oksana; Zhilina, Oxana Mihailovna; Garsiya, Ekaterina Robertovna; et al.
Abstract : Genistein is an isoflavone first isolated from the brooming plant Dyer's Genista tinctoria L. and is widely distributed in the Fabaceae family. As an isoflavone, mammalian genistein exerts estrogen-like functions. Several biological effects of genistein have been reported in preclinical studies, such as the antioxidant, anti-inflammatory, antibacterial, and antiviral activities, the effects of angiogenesis and estrogen, and the pharmacological activities on diabetes and lipid metabolism. The purpose of this review is to provide up-to-date evidence of preclinical pharmacological activities with mechanisms of action, bioavailability, and clinical evidence of genistein. The literature was researched using the most important keyword "genistein" from the PubMed, Science, and Google Scholar databases, and the taxonomy was validated using The Plant List. Data were also collected from specialized books and other online resources. The main positive effects of genistein refer to the protection against cardiovascular diseases and to the decrease of the incidence of some types of cancer, especially breast cancer. Although the mechanism of protection against cancer involves several aspects of genistein metabolism, the researchers attribute this effect to the similarity between the structure of soy genistein and that of estrogen. This structural similarity allows genistein to displace estrogen from cellular receptors, thus blocking their hormonal activity. The pharmacological activities resulting from the experimental studies of this review support the traditional uses of genistein, but in the future, further investigations are needed on the efficacy, safety, and use of nanotechnologies to increase bioavailability and therapeutic efficacy.